EFFECT OF WATER AS LUBRICANT ON FRICTION AND WEAR PROPERTIES OF CGRP COMPOSITE EVALUATED BY POD AND BOR TECHNIQUES - YOUSIF, B. F.; EL-TAYEB, N. S. M. (WORLD SCIENTIFIC PUBL CO PTE LTD, 2007)
In the current decade, introducing water as a lubricant for tribo-engineering materials has become a concern for many researchers. In the present study, the wear and friction characteristics of a polyester ( CGRP) composite reinforced with a chopped glass mat (CSM) 450 g/m(2) was investigated under dry and wet conditions against a polished, stainless steel counterface. Two techniques known as Pin on Disc ( POD) and Block on Ring (BOR) were used to perform the experimental tests. The tests were conducted on a newly developed machine that could carry out both techniques. The effects of the applied load ( 30, 50, 70, 100N), sliding velocity (2.8 and 3.9m/s), and test duration (5-30 min) on wear rates and the coefficients of friction were investigated. Under dry conditions, the temperature of the interface was measured with an infrared thermometer. Worn surface morphologies of the composite were observed with a scanning electron microscopy ( SEM) and damage features were characterized. The results showed that the test technique and conditions had significant influences on the wear and friction performance of the CGRP composite. The presence of water as a lubricant enhanced the wear and friction characteristics of the composite as determined by both POD and BOR, and the SEM micrographs demonstrated several damage features under dry/wet conditions, e. g., deformation, as well as fiber peeling, cracking, and cutting.